Let’s Go Halves Scheme: An Evaluation of Effectiveness and Efficiency - Boonyaratanakornkit, Thanaphon; Withitwinyuchon, Nutthathirataa (Journal of Contemporary Social Sciences and Humanities, 2025)
The COVID-19 pandemic has had a significant impact on the Thai economy, leading the government to implement economic stimulus measures to assist those affected. One of these measures is the Let’s Go Halves Program, which focuses on a co-payment system between the government and the public while also supporting small entrepreneurs. This research aims to qualitatively investigate the effectiveness and efficiency of the program, as well as identify any problems encountered during its implementation from 2020 to 2021. The study also provides recommendations for future improvements to similar program. To gather opinions, ten open-ended interviews were conducted and analyzed comparatively with governmental documents. This research found that the scheme is based on the concept of the multiplier effect, in which stimulating demand factors generate purchasing power that leads to other economic activities. Additionally, the study examined six similar economic stimulus policies from different countries and found that the Let’s Go Halves Program addressed common issues such as people using government subsidies as savings and government assistance not reaching small entrepreneurs. From 2020 to 2021, this program was found to be an effective economic stimulus policy, despite challenges with program accessibility, technical compatibility, inequity in program participation, and program transparency that require attention.